Development of A Dyscalculia Identification Test Instrument - Budi Azhari; Rahmah Johar; Evi Ramadhani; Mailizar Mailizar (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2024)
Abstract: This research aims to develop a dyscalculia test instrument for early identification of children with dyscalculia learning disorders through a series of validity and reliability tests involving various experts from various related fields. This research uses the Tessmer model in developing test instruments through several stages, including: preliminary, self evaluation, prototyping (expert reviews, one-to-one, and small group), and field tests. The research results show that each research variable, namely X1 (type A), X2 (type B), and X3 (Dyscalculia), has met high validity. All question items in these three variables have an r-value that exceeds the r-table, ensuring that the instrument measures what it is intended to measure and reflects the construct accurately. The reliability test results show that each variable has a raw_alpha above 0.80, which reflects very high reliability. This shows that the instrument has the ability to produce consistent and reliable results under repeated use and on different samples. So that the instrument developed can be used to identify and diagnose dyscalculic children in helping dyscalculic children overcome the difficulty of learning mathematics.Abstrak: Penelitian ini bertujuan untuk mengembangkan instrumen tes diskalkulia untuk mengidentifikasi awal anak dengan gangguan belajar diskalkulia melalui serangkaian uji validitas dan reliabilitas yang melibatkan berbagai pihak ahli dari berbagai bidang terkait. Penelitian ini menggunakan model Tessmer dalam mengembangkan instrumen tes melalui beberapa tahapan, antara lain: preliminary, self evaluation, prototyping (expert reviews, one-to-one, dan small group), dan field test. Hasil penelitian menunjukkan bahwa setiap variabel penelitian, yakni X1 (tipe A), X2 (tipe B), dan X3 (Diskalkulia), telah memenuhi validitas yang tinggi. Semua item soal di ketiga variabel tersebut memiliki r-hitung yang melebihi r-tabel, memastikan bahwa instrumen mengukur apa yang dimaksudkan untuk diukur dan mencerminkan konstruk dengan akurat. Hasil uji reliabilitas menunjukkan bahwa setiap variabel memiliki raw_alpha di atas 0,80, yang mencerminkan reliabilitas yang sangat tinggi. Ini menunjukkan bahwa instrumen memiliki kemampuan untuk menghasilkan hasil yang konsisten dan dapat diandalkan dalam penggunaan berulang dan pada sampel yang berbeda. Sehingga instrumen yang dikembangkan dapat digunakan keperluaan identifiksi dan mendiagnosa anak diskalkulia dalam membantu anak diskalkulia mengatasi masalah kesulitan belajar matematika.